Saber, conhecimento e poder: relações de mediação entre agricultores ecologistas e técnicos no Núcleo Missões da Rede Ecovida de Agroecologia - Bremm, Cristina (2018)
In the modernization process of agriculture, which was implemented and encouraged in Brazil since the 1960s, was conformed a hierarchical model of technical assistance, the diffusionist-innovative model, from which the rural extension agents started propagating that traditional agriculture models, practiced by settlers, were backward, inefficient and archaic, and should be replaced by the practice of a “modern” and efficient agriculture in which would be used, starting from the appropriate technical guidance and credit acquired from banks, machines, equipments and industrial inputs. Against the authoritarian methodology of guidance which was adopted by rural extension agents, the social movements from camp built another model based on your experiences and some of them have incorporated agroecology as a model for agriculture. Considering that, this research aims to analyze the mediation relations between ecological farming families, agricultural technicians and leaders linked to Missões Nucleus from Ecovida Agroecology Network, given that these agents propose to build horizontal relations. To carry out this research documentary records were consulted, interviews and observations were made during the meetings and activities in which participated througouth the year 2017. The results of the study reveal that the agricultural technicians and leaders of the Missões Nucleus seek to reshape their practices based on the experiences of ecological farming families. In technical assistance are made suggestions about ecological management and crops; workshops are held to enable farmers to master production of organic inputs; and field days in which the most experienced farmers are put in contact with those who seek to solve their production problems. The activities of exchange of experience held at regular meetings among groups of ecological families reveal that farmer-to-farmer learning is highlighted and contributes to more dialogic and participatory technical assistance work. However, even though in practice of technical assistance the agronomists reformulate their academic knowledge in interaction with ecological families, there is interdependence and asymmetry in relationships that are marked by a variable balance of power. The leaders of the Nucleus Missões have different social insertions and in their trajectories conformed cultural and symbolic capitals that allow them to enforce the rules and regulations. This does not prevent farmers from putting up resistance.